The Concept of Islamic Education Reform in Indonesia: Perspectives of Harun Nasution and Nurcholish Madjid - Aswandi Aswandi; Djeprin E. Hulawa; Alwizar (The Future of Education Journal, 2024)
This study aims to analyze Harun Nasution's thoughts on Islamic education reform in Indonesia, examine the Islamic education reform concept proposed by Nurcholish Madjid, and compare the relevance and contributions of both thinkers to Islamic education in the modern era. This research is a literature study (library research) with a descriptive qualitative approach. Data was collected through literature reviews including books, articles, scientific journals, and other sources relevant to the ideas of Harun Nasution and Nurcholish Madjid. A comparative approach was used to analyze the similarities and differences between the thoughts of the two figures. Data analysis was conducted thematically to identify the main concepts and their implications for Islamic education in Indonesia. The results of this study show that Harun emphasized rationality in Islamic education by integrating religious and general knowledge, eliminating the dichotomy in education, and encouraging a more contextual theological reform. He believed that Islamic education should be responsive to the development of modern science. Nurcholish emphasized the importance of pluralism, modernization, and openness in Islamic education. He advocated for education that not only builds religious knowledge but also shapes moral character, tolerance, and openness to modern science. The conclusion of this research is that the ideas of both thinkers complement each other and are relevant for building an adaptive Islamic education system in response to changing times. Harun's focus is more on theological aspects and rationality, while Nurcholish focuses on pluralism and modernity. Both offer strategic solutions to integrate Islamic values with the demands of globalization.